Exploring students’ EFL writing through hypertext design - López, María Eugenia (Colombian Applied Linguistics Journal, 2006)
This research analyzes the processes students undergo when writing hypertexts collaboratively. This qualitative case study provides an overall picture of students’ EFL writing through hypertext design. It is a collaborative experience which explores and documents how students deal with grammatical, textual and pragmatic aspects when writing hypertexts. This study draws upon data collected during a semester conducted with engineering students at a university in 2003. Students’ hypertexts, audio recordings, students’ reflection logs and an interview were used as main data collection sources. Two main categories emerged as a result of triangulating evidence: “Process of collaborative hypertext writing and negotiation” and “Use of concept mapping and other strategies to overcome difficulties in hypertext writing”.